Refractive outcomes after cataract surgery with primary lens implantation in infants. Issue 11 (26th July 2006) - Barry, J-S; Ewings, P; Gibbon, C; Quinn, A G
Abstract : Aims: To show the refractive outcomes, accuracy of intraocular lens power selection, and visual outcomes and complications in infants undergoing cataract surgery. Methods: The refraction (spherical equivalent) of 14 operated eyes in 8 children aged <1 year was plotted over time. Preoperative and final recorded visual acuities were assessed. Results: The median follow-up was 37.25 months. The median initial postoperative refraction was +6.75 dioptres. Conclusions: Refractive outcomes for each eye were not entirely predictable and were variable between infants. However, there was a consistent pattern in each infant who underwent bilateral surgery, with both eyes following a similar pattern of refractive change with time: a decreasing myopic shift was seen in 8 eyes, possibly demonstrating emmetropisation. The two unilateral cases appeared to show a linear myopic shift. 4 eyes in 2 patients did not follow a myopic shift curve and one of these patients showed an early trend towards increased hyperopia. Definite causes for this erratic refractive change were not identified. A postoperative refraction >4.5 dioptres avoided early onset myopia. The range of difference between postoperative and predicted refraction using SRK-T was −2.85 to 2.97 dioptres. Most of the visual results are encouraging compared with historical data in older children.